Why Work Overtime? A Systematic Review on the Evolutionary Trend and Influencing Factors of Work Hours in China - Bei Liu; Hong Chen; Xingxing Yang; Congmei Hou (Frontiers Media S.A., 2019)
Objectives: Research that examined changes in the laws in respect to work hours was of great importance for understanding its current status and causes. However, most research on work hours in China is still conducted using self-reported questionnaires, which lack coherence and depth, and are inadequate for exploring the evolutionary trend of work hours and its mechanism.Methods: This study examined the evolutionary trend of Chinese employees' work hours by employing a cross-temporal meta-analysis, and employed the entropy weight method to analyze each influencing factor. The China National Knowledge Infrastructure (CNKI), VIP information and WanFang database were searched for Chinese-language peer-reviewed literature, and Google Scholar and the Web of Science were searched for related literature in the English language.Results: A total of 36 pieces of literature were identified as having satisfied the quality standards for screening. The results indicated that work hours in China show a significant fluctuating upward trend. Most of the recent studies on work hours in China were cross-provincial investigations, and the issue of overtime among migrant workers has become the key focus of current research. Most studies on the work hours of Chinese employees were conducted in a manner whereby scholars played a leading role while the government assisted. Thus, government-led, intensive and nationwide research needs to be launched.Conclusions: The issue of work hours in China should be taken seriously. The main influencing factors included survival indicators, such as labor market conditions and levels of medical security levels, followed by power-assisted indicators, such as personal income and distribution, while labor protection had a minimal impact. This study will contribute to a better understanding of the essence of work hours among Chinese employees, and will also help to provide a theoretical basis for further intervention study related to overtime work.